Analisis Penerapan Sistem Informasi Akuntansi Penerimaan dan Pengeluaran Kas Berbasis Web: Studi Kasus pada PT Multi Star Rukun Abadi (Lembaga Pengembangan Kinerja Dosen, 2025)
The purpose of this study is to identify the procedures of the accounting information system for cash receipts and disbursements at PT Multi Star Rukun Abadi prior to the implementation of the web-based system, the timeline of its adoption, and the procedures involved in the web-based accounting information system for cash receipts and disbursements. This study also aims to explore the features available in the web-based system, identify the individuals responsible for its implementation, examine the challenges faced by PT Multi Star Rukun Abadi during its adoption, and analyze the benefits gained from implementing the web-based accounting information system for cash receipts and disbursements. The research method used is qualitative descriptive by collecting data from interviews, documentation and observation. The findings of this study indicate that the web-based system helps accelerate cash recording, although challenges such as user training and system integration still exist. The originality of this research lies in its focus on the web-based accounting information system for cash receipts and disbursements at PT Multi Star Rukun Abadi. This study uses a case study approach.